Using temperament and character dimensions (TCI) to analyze the personality profiles of adults and older adults with cancer managed in outpatient settings - Vespa, Anna; Giulietti, Maria Velia; Fabbietti, Paolo; Di Rosa, Mirko; Gattafoni, Pisana; Berardi, Rossana; Arnaldi, Giorgio; Balercia, Giancarlo; Spatuzzi, Roberta (Frontiers in Psychology, 2024)
This study aimed at investigating profiles of personality evaluated by temperament and character dimensions(TCI) in 638adult and older adults patients (CP) affected by breast, colon, lung, and other kinds of cancer, recently diagnosed (female and male) . Tests: Temperament and Character Inventory(TCI). Statistical analysis: cluster K-Means-analysis: personality traits.Two different personality profiles"Low self-determination and pessimism"-(Profile 1) and "Self-determination and self-caring (medium)"-(Profile 2). The following significant differences emerge in the TCI dimensions between the two profiles: Temperament-Novelty-Seeking(NS)(p<0.001);Harm-Avoidance(HA)(p<0.001);Reward-dependence(RD)(p<0.001);Persistence(PS)(p<0.001); Character-Self-directness(SD)(p<0.001); Cooperativeness(C) (p>0.001); Self-transcendence (ST)(p<0.001). No differences in the two profiles between adult and elderly patients.Profile-1-Low self-determination and pessimism": Patients with this profile present -low resistance to frustration, poor search for novelties and solutions (NS); anxiety and pessimism (medium HA); high social attachment and dependence on the approval of others (medium-high RD); low self-determination (PS); as dimensions of Temperament; and a medium-low selfdirection, low autonomy and ability to adapt (SD-medium-low), medium cooperativeness (C) and low self-transcendence (ST) as character dimensions.Profile-2-Self-determination and self-caring(medium)" Patients with this profile have resistance to frustration, ability to search for novelties and solutions (medium-NS), low anxiety and pessimism (HA), low social attachment and dependence on approval (medium-low-RD); determination (medium-high PS) as dimensions of temperament and autonomy and capacity for adaptation and self-direction (SD, capacity for cooperation (high-CO) and self-transcendence (medium-high-ST) as character dimensions.4Conclusions Personality screening allows you to better understand the difficulties of the individual patient and plan targeted psychotherapeutic interventions that promote quality of life and good adaptation to the disease path.